Math 310 Class Notes 5: the Recursion Theorem for N

Math 310 Class Notes 5: the Recursion Theorem for N

Math 310 Class Notes 5: The Recursion Theorem for N In this set of notes we will tighten a loose end that has been left dangling. Namely, in Class Notes 3 we used the word "assign" when we defined the notion of + for N (see Definition 2 of the notes). The word "assign" actually means we have a function that does the assignment. To be precise, we have the following theorem. Theorem 1. (The recursion theorem) Let c be a fixed natural number and let f : N ! N be a function. Then there is a unique function g : N ! N such that g(1) = c and g(x0) = f(g(x)) for all x 2 N. Before proving this theorem, let us see a few applications. Application 1. Consider the function f : N ! N given by f : x 7! x0: Fix a number m 2 N. Then by the recursion theorem there is a function g such that g(1) = m0 and g(x0) = f(g(x)) for all x 2 N. Let us now define m + n := g(n) for all n 2 N. Theorem 2. Fix m 2 N. We have m + n0 = (m + n)0 for all n 2 N. Proof. m + n0 = g(n0) = f(g(n)) = f(m + n) = (m + n)0. Slightly harder to verify is the following. Theorem 3. Fix m 2 N. We have m0 + n = (m + n)0 for all n 2 N. Proof. m + n = g(n) for all n 2 N, where g(1) = m0 and g(n0) = f(g(n)). Likewise, m0 + n = h(n) for all n 2 N, where h(1) = (m0)0 and h(n0) = f(h(n)). Let S be the set of all n 2 N such that m0 + n = (m + n)0. We first show 1 2 S. Now m0 + 1 = h(1) = (m0)0 while m + 1 = g(1) = m0, so that m0 + 1 = (m0)0 = (m + 1)0. Thus 1 2 S. Next suppose n 2 S. We establish that n0 2 S. That n 2 S means m0 + n = (m + n)0; which is the induction hypothesis. Therefore, by the preceding theorem and the induction hypothesis we have m0 + n0 = (m0 + n)0 = ((m + n)0)0 = (m + n0)0: Therefore, n0 2 N and so S = N. That is m0 + n = (m + n)0 for all n 2 N. 1 2 This theorem is what we have seen in class. The advantage of this approach via the recursion formula is that we can take care of m + n for all m and n at one stroke. Application 2. Fix m 2 N. Consider the function f : N ! N given by f : x 7! x + m: Then by the recursion theorem there is a function g : N ! N such that g(1) = m and g(x0) = f(g(x)). We define m · n := g(n) for all n 2 N. Exercise. Prove that m · n0 = m · n + m and m0 · n = m · n + n for all n 2 N. Application 3. Fix a 2 N. Consider the function f : N ! N given by f : x 7! ax: Then by the recursion theorem there is a function g : N ! N such that g(1) = a and g(x0) = f(g(x)). We define an := g(n): Exerxise. By the mathematical induction, prove that am+n = am · an and (am)n = amn. Now let us look at the proof of the recursion theorem. Proof. Existence of g. By definition, a function g : N ! N is a special sort of subset of N × N. Recall that g(1) = c means (1; c) 2 g and g(x0) = f(g(x)) means that if we let y = g(x), i.e., let (x; y) 2 g, then (x0; f(y)) 2 g as this just says g(x0) = f(g(x)) = f(y): Motivated by this, let us begin to construct the function g by consid- ering the set S, where S := fA ⊂ N × N : (1; c) 2 A and (x; y) 2 A implies (x0; f(y)) 2 Ag: S is not empty since N × N 2 S. Consider the set g := \A2S A; which consists of elements common to all A 2 S. Now (1; c) 2 g since it is in all A 2 S. Moreover, if (x; y) 2 g then (x; y) 2 A for all A 2 S. But then (x0; f(y)) 2 A for all A 2 S so that 3 (x0; f(y)) 2 g. We conclude therefore that g is in fact an element of S; it is the smallest element of S. We now prove that g is a function from N to N. First we show that the domain of g is N. Let T be the subset of n 2 N such that there is a z 2 N for which (n; z) 2 g. Now 1 2 T since (1; c) 2 g. Suppose n 2 T . Then (n; z) 2 g for some z 2 N. This gives (n0; f(z)) 2 g. Hence n0 2 T . It follows by mathematical induction that T = N. That is, the domain of g is N. Secondly, we show that each domain element of g is mapped to a unique target element. To this end, consider the set U := fx 2 N : (x; y); (x; z) 2 g imply y = zg: We show 1 2 U. Suppose this is not the case. That is, suppose we have (1; z), in addition (1; c) 2 g, where z =6 c. Then the set g nf(1; z)g would be a member of S (WHY?). But this contradicts the fact that g is already the smallest element of S. Thus, 1 2 U. We show that if x 2 U then x0 2 U. Suppose this is not the case. Then there is an m 2 U so that m0 2= U. Since m 2 U, there is a unique n 2 N with (m; n) 2 g. As a consequence (m0; f(n)) 2 g. Since m0 2= U, there is an (m0; z) 2 g, in addition to (m0; f(n)) 2 g, where z =6 f(n). But then g n f(m0; z)g is an element of S that is even smaller than g (WHY?), which is absurd. The mathematical induction then says that U = N. In conclusion, g is a function. Uniqueness of g. Suppose we have two functions g1 and g2 satisfying g1(1) = c = g2(1) 0 0 and g1(x ) = f(g1(x)) and g2(x ) = f(g2(x)) for all x 2 N. Let us consider the set V := fn 2 N : g1(n) = g2(n)g: 1 2 V because g1(1) = g2(1) = c. If n 2 V , then g1(n) = g2(n), so that 0 0 g1(n ) = f(g1(n)) = f(g2(n)) = g2(n ); which implies n0 2 V . Hence V = N by the mathematical induction. That is, g1 = g2. .

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    3 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us